PENGARUH BURNOUT, WORK FAMILY CONFLICT DAN LINGKUNGAN KERJA TERHADAP TURNOVER INTENTION PT. BANK SYARIAH INDONESIA - Mardiansyah, Adi; Arianto, Tezar (Jurnal Entrepreneur dan Manajemen Sains (JEMS), 2025)
A phenomenon that often occurs is that organizations have such good performance that they can be damaged, either directly or indirectly by various employee behaviors that are difficult to prevent. One form of this behavior is the desire to move (turnover intention) which leads to the employee's decision to leave his or her job. The purpose of this study is to find out burnout, work family conflict and work environment towards turnover intentionPT. Bank Syariah Indonesia Bengkulu (BSI).This type of research is a descriptive quantitative approach. The population in this study is 42 employees. The data collection techniques in this study are observation and questionnaires. The data analysis techniques used were multiple linear regression, determination coefficient, and hypothesis test. It was found that bornout (X1) had a positive effect on  the Turnover Intention (Y) of PT. Bank Syariah Indonesia Bengkulu. This is proven from the hypothesis test with the t-test obtained t-> ttable (3,058,>1,977). Work Family Conflict (X2) has a positive effect on  the Turnover Intention (Y) of PT. Bank Syariah Indonesia Bengkulu. This is proven from the hypothesis test with the t-test obtained t-> ttable (-.060>1.977). The Work Environment (X2) has a positive effect on  the Turnover Intention (Y) of PT. Bank Syariah Indonesia Bengkulu. This is proven from the hypothesis test with the t-test obtained tcal> ttable (2,908>1,977).Bornout (X1), Work Family Conflict (X2), and Work Environment (X3) have an effect on  consumer Turnover Intention (Y). This can be seen from the hypothesis test jointly (Simultaneous) Ftable> Fcal (175,214 > 3,940). This is evidenced by the correlation analysis R = 0.949 (94.9%) and is almost close to 1. As well as the determination coefficient of R2 = 0.949 or around 94.9% while 5.1% Keywords :Burnout, work family conflict, work environment, turnover